2015
DOI: 10.1007/s10096-015-2398-6
|View full text |Cite
|
Sign up to set email alerts
|

Point prevalence of appropriate antimicrobial therapy in a Dutch university hospital

Abstract: Antimicrobial stewardship teams have been shown to increase appropriate empirical antibiotic therapy and reduce medical errors and costs in targeted populations, but the effect in non-targeted populations is still unclear. The aim of this study was to determine the prevalence of inappropriate antibiotic use in a large university hospital and identify areas in which antimicrobial stewardship will be the most effective. In a point prevalence survey we assessed the appropriateness of antibiotic therapy using an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 26 publications
2
29
1
Order By: Relevance
“…Meanwhile, we obtained the example of ceftriaxone which was given 3 times a day in children weighing 19 kg. The results of this study in the IIB category were judged to be greater when compared with previous studies, showing that 6.8% of prescribed antibiotics were not used properly, in part, because of incorrect therapy duration or incorrect dose intervals [20].…”
Section: Discussioncontrasting
confidence: 78%
“…Meanwhile, we obtained the example of ceftriaxone which was given 3 times a day in children weighing 19 kg. The results of this study in the IIB category were judged to be greater when compared with previous studies, showing that 6.8% of prescribed antibiotics were not used properly, in part, because of incorrect therapy duration or incorrect dose intervals [20].…”
Section: Discussioncontrasting
confidence: 78%
“…A study from Rotterdam reported that 34.4% of hospitalized patients used prophylactic antibiotics, but this included patients using surgical prophylaxis administered in the operating theatre [9]. A study from the Radboud University hospital in the Netherlands reported a percentage of 19.1% for medical prophylaxis, but only antibiotics were investigated [10] .…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are indispensable part of modern medicines and the cornerstone for treating bacterial infections across healthcare sectors [1][2][3][4][5]. They are now one of the most common medicines prescribed in hospitals and across sectors [1,6,7] to reduce morbidity and mortality [1,2,7,8].…”
Section: Introductionmentioning
confidence: 99%